THE PH DEPENDENCE OF NATURAL ORGANIC MATTER SORPTION TO NANOPARTICLES AND ITS ABILITY TO STABILIZENANOPARTICLES IN AQUEOUS SOLUTIONS - Phenny Mwaanga; Elizabeth R. Carraway; Mark A. Schlautman (European Scientific Journal, ESJ, 2014)
Several studies have demonstrated that natural organic matter (NOM) can reduce toxicity of most toxic chemicals through sorption /complexation processes. In the area of nanoecotoxicology, this has also been demonstrated. The sorption of NOM on to the nanoparticles (NPs) has further been lauded for particle stabilization and hence lessening the effect of particle aggregation. Comprehensive understanding of NOM – NPs interaction can help improve our predictive capability of fate and transport of nanomaterials in the aquatic environment. In this study, the particle stabilization of NOM on both sonicated and nonsonicated TiO2NPs at different pH values was examined. The study further examined the sorption of NOM to TiO2NPs at the same pH values. The unsorbed NOM was separated from the sorbed by both ultracentrifugation and 50 nm polycarbonate membrane filters (the results of both methods agreed to within 3%). The dynamic light scattering (DLS) technique was used to characterize the aggregates. The PALS Zeta potential analyzer was used to estimate surface charge. The total organic carbon was measured by the Total Organic Carbon Analyzer- Shimadzu (TOC-VCPH). The results indicated that the NPs stabilization by NOM was pH dependent and was more pronounced at higher pH, but lowest at pH values close to the point of zero charge (PZC) for the TiO2NPs. The ability of NOM to stabilize nonsonicated NPs was found to be mild. As expected, the sorption results showed that the least amount of NOM was sorbed at higher pH, despite the observation that the highest stabilization occurred at higher pH.